Status Trofik Dan Daya Tampung Beban Pencemaran Waduk Sutami - Juantari, Gilang Y.; Sayekti, Rini Wahyu; Harisuseno, Donny (Jurnal Teknik Pengairan: Journal of Water Resources Engineering, 2013)
Sutami reservoir water quality declined due to the high character of organic waste disposal. This degradation is attributed by contamination due to natural erosion and agricultural waste, is also due to the entry of domestic waste (household) and industrial waste in upstream reservoirs Sutami. The addition of organic and inorganic materials in the form of waste into the reservoir in addition to changing the chemical composition of water, also affects the biological properties of these waters.The purpose of this study was to determine the load capacity of pollution that occurred in the reservoir Sutami and trophic status based on the Regulation of the Minister of Environment No. 28 of 2009.The study was conducted in the reservoir Sutami using primary and secondary data. Sampling locations in the central part of the reservoir at a depth of 0.3 m and 5 m and the lower reaches of the reservoir at a depth of 0.3 m and 10 m. Observed variables include levels of P (Phosphorus), water clarity, and Chlorophyll-a is contained in water reservoirs Sutami. Chlorophyll-a and the brightness of the water obtained from the sampling process independently, while the number of secondary data from phosphorus (P) obtained from Perum Jasa Tirta I from January 2010 until May of 2011. The data obtained were analyzed with descriptive statistics showing the average and standard deviation.The results showed that the condition of the water reservoir was contaminated Sutami in moderate to severe, both in the location of reservoirs upstream and downstream reservoirs. Trophic status of reservoirs Sutami is eutrofik to hypertrophic occurs on the downstream and middle reservoirs. Impacts arising from pollution levels that occur in the Sutami reservoir is the potential for algae bloom due to the high amount of phosphorus and chlorophyll-a. Load carrying capacity of the reservoir pollution Sutami for total phosphorus (kg / year) at the upstream location; 39 kg P / year, the middle; 195 kg P / year and downstream; 178.5 kg P / year.Keywords: pollution, trophic status, chlorophyll-a, reservoirs Sutami